An efficient and environmentally friendly route for PbS crystal recovery from lead ash generated in tin removal section (LATR) via high-speed leaching and recrystallization method - Feng Y.; Peng X.-Q.; Shi H.-H.; Zhang W.; Zuo Q.-T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper mainly investigated the synthesis of a high purity PbS crystal directly from lead ash which was collected from Tin ash removal process (LATR). The LATR was firstly disposed by nitric acid leaching system to generate the lead nitrate solution. The PbS crystal was prepared by mixing the lead nitrate solution with the sodium sulfide at the room temperature (25°C). The effects of molar ratio of HNO3 to Pbin the LATR on Pb leaching efficiency was investigated, demonstrating that the Pb leaching efficiency could attain to 82.9 % at molar ratio of 3. The leaching ratio of As, Cu, Fe, and Al generally increased with increasing molar ratio of HNO3 to Pbin the LATR, while 99.99 wt% of Sn was still left in the residue. In the process of generating PbS crystal from the leaching solution, the yield of PbS crystal increased with increasing molar ratio of Na2S to Pbin the filtrate. The yield of PbS crystal could up to 93.1% at a molar ratio of 1.5. Overall, this method proved to be an efficient and environmental friendly route for synthesis of high quality PbS crystal directly from the common lead containing waste from the lead ore or secondary smelting factory.